National Security of the Republic of Poland: Strategic Aspects (Economic and Political Thought, 2013)
The article presents basic conditions and conclusions of the first in thehistory of Poland Strategic Review of National Security, which aimed at findinganswers to the questions about the overall national security of Poland,formulating a forecast of changes in its conditions in the perspective of20 years’ time and strategic directions of developing the security of Polandresulting from them. The Strategic Review of National Security was a pioneering initiative.It started a new quality in the development of the Polish strategic culture andattracted a lot of attention at home and abroad. Its success is that it has triggereda widespread debate about security. The success will be complete if thereview results in transformational activities aimed at creating an integratedsystem of national security.